CODE-SWITCHING AS A PEDAGOGICAL RESOURCE IN MULTILINGUAL CLASSROOMS - Sofia Alvarez, Liam O'Connor (International Journal of Literature and Language Studies, 2024)
This article examines code-switching as a pedagogical resource in multilingual classrooms through a focused qualitative lens. Drawing on observed classroom interactions in multilingual secondary and tertiary language lessons, the study uses classroom discourse analysis with attention to interactional sequences, teacher moves, and learner uptake to identify how meaning, voice, and interpretation are shaped in literary and linguistic practice. The analysis shows that strategic code-switching reduced anxiety and increased participation, teacher-switches supported clarification without weakening target-language exposure, while the third finding highlights how textual structure or interactional pattern helps sustain the broader effect. The paper argues that close attention to language form remains essential for understanding how literary texts and communicative events produce emotion, identity, and social meaning. It also demonstrates that careful reading can connect stylistic detail with wider cultural and pedagogical questions.